Analisis Kualitas Proposal Kegiatan Seminar Mahasiswa Jurusan Kimia Menuju Program Berkualitas - Bella Junita Sari Tamba; Dilla Rama Dina; Nurfrida Nurfrida (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to analyze the quality of seminar proposals submitted by Chemistry Department students in an effort to achieve a well-structured and high-quality program. The research employs a descriptive qualitative method with data collection through document analysis. The research steps include (1) identifying the structure and organization of the proposals, (2) analyzing linguistic aspects such as spelling, diction, and sentence structure, (3) evaluating the clarity of objectives, methodology, and budget, and (4) categorizing errors and discussing recommendations for improvement. The results show that several proposals contain deficiencies, particularly in linguistic accuracy and systematic writing. Some proposals exhibit inconsistencies in structure, lack clarity in defining objectives and expected outcomes, and do not fully adhere to academic writing standards. Therefore, improvement strategies are necessary to enhance the quality of proposals, making them more systematic, clear, and effective. Strengthening proposal writing skills will increase the likelihood of approval and support the successful implementation of high-quality seminars.